PROXIMATE ANALYSIS AND VITAMIN C CONTENT IN YELLOW COCONUT (Cocos Nucifera L): ANALISIS PROKSIMAT VITAMIN C DAN ANTIOKSIDAN PADA SAMPEL KELAPA KUNING (Cocos Nucifera) - Fatahu; Baihaqi; Ekacahyana Mandasari; Wa Ode Mulyana; Andi Laila Nugrawati (PT. ROCE WISDOM ACEH, 2026)
This study aims to analyze the nutritional composition and antioxidant activity of yellow coconut (Cocosnucifera), focusing on both the flesh and water parts. The analyzed parameters include vitamin C, protein, carbohydrate, fat, moisture, ash content, and antioxidant activity using the DPPH method. The results showed that yellow coconut flesh contains more nutrients than its water, with a vitamin C content of 237.67 mg/100g, protein at 1566 ppm, and fat at 93.67%. Moisture and ash contents were 91.33% and 0.82%, respectively. These findings suggest that yellow coconut, particularly its flesh, has significant potential as a functional food to support health and warrants further development in the natural food industry